Pension Information and Women's Awareness - Marta Angelici; Daniela Del Boca; Noemi Oggero; Paola Profeta; Maria Cristina Rossi; Claudia Villosio (Institute of Labor Economics (IZA), 2020)
We explore the role of financial and pension information in increasing women's knowledge and awareness of their future pension status, and consequently, in reducing the gender pension gap. A representative sample of 1249 Italian working women were interviewed to assess their knowledge about pensions and financial issues and about their own savings and personal wealth planned for retirement. The responses showed that their knowledge and awareness of retirement planning was limited. We then ran a randomized experiment to evaluate the effect of increased information regarding pensions on women's awareness, knowledge, and behaviors. Women in the treated group were provided information in the form of three short online tutorials. A follow-up survey shows that these women became more interested and aware of pension schemes and retirement options after completing the tutorials and were more likely to be better informed and keen to obtain further information. When looking at changes in behavior, we find that treated women who are closer to retirement are more likely to believe that they would make different work-life decisions if they received specific pension information in a timely fashion. They are also more likely to have a supplementary pension fund if they are concerned about their standard of living after retirement.
Keywords: H31; G51; J22; 330; women; pension; savings; financial education